Quantitative Evaluation of the Lethal Impact of High Temperature from Summer Sunlight on the Life Stages of the Sawtoothed Grain Beetle, Oryzaephilus surinamensis L. Under the climatic conditions of the city of Kirkuk. - Mohammed, Nagham Abdulghani; Qader, Fadel Abbas (Universitas Muhammadiyah Sidoarjo, 2026)
This study aimed to evaluate the lethal efficacy of high temperatures from sunlight during July and August on the larvae and adults of the sawtoothed grain beetle, Oryzaephilus surinamensis L. Insect colonies were obtained from local wheat grain stores in Kirkuk markets, containing adult individuals of this insect. They were utilized by rearing them in an incubator at 30±2°C and 70±5% relative humidity in the laboratories of the College of Education for Women, Department of Life Sciences. The resulting larvae and adults were then used to conduct the experiments of this study. Advanced-stage larvae were taken and placed in Petri dishes at a rate of ten larvae per dish. Similarly, one-week-old adults were taken and placed in Petri dishes at a rate of ten adults per dish, with three replicates for each treatment. They were then exposed to direct sunlight using three exposure periods (10:00 AM, 12:00 PM, and 2:00 PM) for durations of (15, 30, 45) minutes during July and August 2025 under the conditions of Kirkuk city.